2012
DOI: 10.5966/sctm.2012-0058
|View full text |Cite
|
Sign up to set email alerts
|

Glioma-Initiating Cell Elimination by Metformin Activation of FOXO3 via AMPK

Abstract: MEDICINE 2012;1:811-824

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
184
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(196 citation statements)
references
References 36 publications
7
184
5
Order By: Relevance
“…Moreover, these strong anticancer actions were also supported by Kaplan-Meier analyses, which showed a statistically significant survival benefit. Sato el al 22 observed that metformin treatment alone significantly inhibited tumor growth in an orthotopic mouse model, which was not seen in our experiment. They used the same dose of metformin (500mg/kg) with the same delivery method.…”
Section: Neurooncologymentioning
confidence: 35%
See 2 more Smart Citations
“…Moreover, these strong anticancer actions were also supported by Kaplan-Meier analyses, which showed a statistically significant survival benefit. Sato el al 22 observed that metformin treatment alone significantly inhibited tumor growth in an orthotopic mouse model, which was not seen in our experiment. They used the same dose of metformin (500mg/kg) with the same delivery method.…”
Section: Neurooncologymentioning
confidence: 35%
“…18,19 Other research based on the selective toxicity of metformin toward cancer stem cells (CSCs), however, supports a "reverse Warburg effect, " arguing that CSCs are more dependent on oxidative phosphorylation. 15,22,23 Viale et al 20 demonstrated that the surviving cancer cells that are responsible for tumor relapse have features of CSCs and depend on oxidative phosphorylation for their survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mei et al42 further showed that p38 MAPK activation contributes to an increase in CSC population and metastasis. It has been reported that radioresistant glioblastoma stem cells acquired enhanced AMPK activity and in normal human mammary epithelial cells AMPK mediated the mammosphere formation, indicating that AMPK might involve in regulating the self‐renewal and therapeutic resistance of CSCs 38, 39. Our study showed that Sme induced apoptosis via activating the p38 MAPK and AMPKα pathways in MCF7‐Nanog cells.…”
Section: Discussionsupporting
confidence: 49%
“…There is growing evidence supporting that p38 MAPK and AMPK play crucial roles in cancer cell growth, proliferation, survival 38, 39, 40. Meng et al41 reported that p38 MAPK exhibits overexpression in highly metastatic human and mouse breast cancer cell lines and promotes basal‐like and metastatic properties in breast tumor samples.…”
Section: Discussionmentioning
confidence: 99%